Efficient production of pyruvate from DL-lactate by the lactate-utilizing strain Pseudomonas stutzeri SDM. - Chao Gao; Jianhua Qiu; Cuiqing Ma; Ping Xu (PLoS ONE, 2012)
BACKGROUND: The platform chemical lactate is currently produced mainly through the fermentation of sugars presented in biomass. Besides the synthesis of biodegradable polylactate, lactate is also viewed as a feedstock for the green chemistry of the future. Pyruvate, another important platform chemical, can be produced from lactate through biocatalysis. METHODOLOGY/PRINCIPAL FINDINGS: It was established that whole cells of Pseudomonas stutzeri SDM catalyze lactate oxidation with lactate-induced NAD-independent lactate dehydrogenases (iLDHs) through the inherent electron transfer chain. Unlike the lactate oxidation processes observed in previous reports, the mechanism underlying lactate oxidation described in the present study excluded the costliness of the cofactor regeneration step and production of the byproduct hydrogen peroxide. CONCLUSIONS/SIGNIFICANCE: Biocatalysis conditions were optimized by using the cheap dl-lactate as the substrate and whole cells of the lactate-utilizing P. stutzeri SDM as catalyst. Under optimal conditions, the biocatalytic process produced pyruvate at a high concentration (48.4 g l(-1)) and a high yield (98%). The bioconversion system provides a promising alternative for the green production of pyruvate.